Symptomatic Cryptococcal Antigenemia Presenting as Early Cryptococcal Meningitis With Negative Cerebral Spinal Fluid Analysis - Ssebambulidde, Kenneth; Kwizera, Richard; Kandole, Tadeo Kiiza; Tugume, Lillian; Kiggundu, Reuben; Mpoza, Edward; Nuwagira, Edwin; Williams, Darlisha A.; Lofgren, Sarah M.; Abassi, Mahsa; Musubire, Abdu K.; Cresswell, Fiona V.; et al. (Clinical infectious diseases, 2019)
Individuals with cryptococcal antigenemia are at high risk of developing cryptococcal meningitis if untreated. The progression and timing from asymptomatic infection to cryptococcal meningitis is unclear. We describe a subpopulation of individuals with neurologic symptomatic cryptococcal antigenemia but negative cerebral spinal fluid (CSF) studies.We evaluated 1201 human immunodeficiency virus–seropositive individuals hospitalized with suspected meningitis in Kampala and Mbarara, Uganda. Baseline characteristics and clinical outcomes of participants with neurologic–symptomatic cryptococcal antigenemia and negative CSF cryptococcal antigen (CrAg) were compared to participants with confirmed CSF CrAg+ cryptococcal meningitis. Additional CSF testing included microscopy, fungal culture, bacterial culture, tuberculosis culture, multiplex FilmArray polymerase chain reaction (PCR; Biofire), and Xpert MTB/Rif.We found 56% (671/1201) of participants had confirmed CSF CrAg+ cryptococcal meningitis and 4% (54/1201) had neurologic symptomatic cryptococcal antigenemia with negative CSF CrAg. Of those with negative CSF CrAg, 9% (5/54) had Cryptococcus isolated on CSF culture (n = 3) or PCR (n = 2) and 11% (6/54) had confirmed tuberculous meningitis. CSF CrAg-negative patients had lower proportions with CSF pleocytosis (16% vs 26% with ≥5 white cells/μL) and CSF opening pressure >200 mmH2O (16% vs 71%) compared with CSF CrAg-positive patients. No cases of bacterial or viral meningitis were detected by CSF PCR or culture. In-hospital mortality was similar between symptomatic cryptococcal antigenemia (32%) and cryptococcal meningitis (31%; P = .91).Cryptococcal antigenemia with meningitis symptoms was the third most common meningitis etiology. We postulate this is early cryptococcal meningoencephalitis. Fluconazole monotherapy was suboptimal despite Cryptococcus-negative CSF. Further studies are warranted to understand the clinical course and optimal management of this distinct entity.
Keywords: cryptococcal meningitis, HIV, diagnosis, fungal antigen, aseptic meningitis